THE EFFECTIVENESS OF HEALTH EDUCATION IN IMPROVING HIV/AIDS KNOWLEDGE AMONG LOW INCOME PEOPLE IN PONDONG BARU VILLAGE - Dewi, Annita Viesta Nirmala; Wahidah, Nurul Jannatul; Muzayyaroh, Muzayyaroh (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: The number of new HIV/AIDs infection has been increasing around the world. A way to decrease this problem is by increasing people awareness through giving health education. Based on some preliminary research, communities in Pondong Baru Village have not enough knowledge about HIV/AIDS.Objective: This study aims to know the effectiveness of health education improving HIV/AIDS knowledge among low income people in Pondong Baru Village.Methods: This research was quasy experimental with pre post-test one group only, conducted in Pondong Baru Village, Paser, East Kalimantan, on 13th December 2021. The population of this research were people in Pondong Baru Village with low income. The sample were as many as 31 peoples selected by purposive sampling. Data collect using questionnaires and the analysis used Wilcoxon signed rank test with SPSS IBM 25 version.Result: Respondents’ classified based on age groups is undefined (9,7 %), 20-40 years old (35,5 %), and >40 years old (54,8 %). Then, respondents’ education levels is no education (16,1 %), primary school (74,2 %), and junior high school (9,7%). Lastly, respondents’ parity is primipara (4,85 %), multipara (90,3 %), nullipara (4,85%). Before intervention, respondents had under average knowledge (93,5) and upper average knowledge (6,5%). After intervention, all respondents’ had upper average knowledge. Knowledge level after intervention (Mean:12.32; SD: 1.05) was higher than before intervention (Mean: 0.32; SD: 1.27) and it was statistically significant (P < 0.001).Conclusion: It can be concluded that health education is effective in improving HIV/AIDS knowledge among low income people in Pondong Baru Village.